The Phenomenon of a Burgher Family in the Early Modern Period - Marećkova, Marie (Karkonoska Państwowa Szkoła Wyższa, 2011)
The function of a burgher family passed through changes depending upon historical conditions and power relations. Every family member had its social role within the family framework. Family members followed stabilised pattern of behaviour influenced by personal motivation. In the era of the early modem period the original forms of social life of the burghers passed through weakening and a polarisation of the male and female role was strengthening. That was the beginning of a gradual division process of home and public sphere leading to a formation of a burgher model of traditional roles of husband and wife. These changes were being reflected in gradual transferring of productive eaming activities from the home sphere to the public sphere.
Keywords: rodzina; mężczyźni; kobieta; mieszczaństwo